Construct Validity of the Comprehensive Assessment of Psychopathic Personality (CAPP): Examining the Internal Structure and Generalizability of CAPP Self-Ratings Across Gender and Ethnicity. (March 2021) - Hanniball, Katherine B.; Hohn, Richard E.; Fuller, Erin K.; Douglas, Kevin S.
The Comprehensive Assessment of Psychopathic Personality (CAPP) is a recently developed conceptual model of psychopathy designed to index the disorder across 33 personality traits. Although recent research has evidenced support for the CAPP model with respect to the convergent, criterion, and predictive validity of CAPP instruments, little work has examined the optimal internal structure and generalizability of the model and associated measures. The present study sought to elaborate on the construct validity and psychometric properties of the CAPP Lexical Self Rating Scale and determine the utility of the instrument across men and women, and individuals of Caucasian and East Asian descent. Within a large sample of self-identified offenders ( N = 1, 414), we found strong support for a three-factor model comprising domains reflecting interpersonal dominance, behavioral disinhibition, and deficient emotional attachment. Analyses examining the generalizability of the model provide further insight into its applicability for diverse populations.